2007
DOI: 10.1590/s0004-282x2007000700015
|View full text |Cite
|
Sign up to set email alerts
|

Interlaminar epidural corticosteroid injection in the treatment of lumbosciatic pain: a retrospective analysis

Abstract: -Lumbosciatica is a common condition which is associated with significant pain and disability. The aim of the present study was to examine the efficacy of interlaminar epidural corticosteroid infiltration in the treatment of lumbosciatic pain. We evaluated retrospectively sixty patients with lumbosciatic pain that a sequential interlaminar epidural administration of 40 mg methylprednisolone in 7 mL bupivacaine 0.25% was administered. Each patient was interviewed and asked about the pain according to visual ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…However, in the remaining 1 study by Laiq et al, (2009) [24], no statistically significant improvement was observed, but 68% of the patients reported pain relief. In another study by Gomez et al, [27] baseline VAS score was ≥6 in 80% patients, and none of the patients had a VAS score of 0-2 at the baseline. At the last follow-up, greater than 70% of the patients achieved a VAS score between 0-5 with 60% of the patients having a VAS score of 0-2, representing a significant improvement post-EI treatment.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…However, in the remaining 1 study by Laiq et al, (2009) [24], no statistically significant improvement was observed, but 68% of the patients reported pain relief. In another study by Gomez et al, [27] baseline VAS score was ≥6 in 80% patients, and none of the patients had a VAS score of 0-2 at the baseline. At the last follow-up, greater than 70% of the patients achieved a VAS score between 0-5 with 60% of the patients having a VAS score of 0-2, representing a significant improvement post-EI treatment.…”
Section: Resultsmentioning
confidence: 96%
“…The NRS was used in 7 studies [1-2, 12, 17, 21, 23, 26], VAS used in 7 studies [16, 19-20, 22, 24, 27-28], and VNRS and JOA used in the remaining 2 studies [29-30]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations